2019
DOI: 10.1016/j.molmet.2019.06.013
|View full text |Cite
|
Sign up to set email alerts
|

β cell responses to inflammation

Abstract: BackgroundThe extended and clinically silent progression of Type 1 diabetes (T1D) creates a challenge for clinical interventions and for understanding the mechanisms that underlie its pathogenesis. Over the course of the development of Type 1 diabetes, studies in animal models and of human tissues have identified adaptive changes in β cells that may affect their immunogenicity and susceptibility to killing. Loss of β cells has traditionally been identified by impairment in function but environmental factors ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 86 publications
(90 reference statements)
0
5
0
1
Order By: Relevance
“…For instance, while in the  cell preparation the number of transcripts per million (TPM) for CD45 in the patient group was 16.4 (mean), the TPM values for the following  cell markers were as follows: INS (Insulin), 125.359; Sodium/potassium-transporting ATPase gamma chain (FXYD2a), 65; GCK (Glucokinase), 20; Homeobox protein Nkx-2.2 (NKX2-2), 28; Synaptotagmin 4 (SYT4), 36; Neurogenic Differenciation 1 (NEUROD1), 27; Homeobox protein Nkx-6.1 (NKX6-1), 27; and MAF BZIP Transcription Factor B (MAFB), 23, indicating that the observed responses are driven, at least in part, by the constitutive cells of the target tissues. Of note, proinflammatory cytokines decrease the expression of several of the  cell markers (3,20,32) described above.…”
Section: Metadata and Global Gene Expression In The Target Tissues Of Different Autoimmune Diseasesmentioning
confidence: 92%
“…For instance, while in the  cell preparation the number of transcripts per million (TPM) for CD45 in the patient group was 16.4 (mean), the TPM values for the following  cell markers were as follows: INS (Insulin), 125.359; Sodium/potassium-transporting ATPase gamma chain (FXYD2a), 65; GCK (Glucokinase), 20; Homeobox protein Nkx-2.2 (NKX2-2), 28; Synaptotagmin 4 (SYT4), 36; Neurogenic Differenciation 1 (NEUROD1), 27; Homeobox protein Nkx-6.1 (NKX6-1), 27; and MAF BZIP Transcription Factor B (MAFB), 23, indicating that the observed responses are driven, at least in part, by the constitutive cells of the target tissues. Of note, proinflammatory cytokines decrease the expression of several of the  cell markers (3,20,32) described above.…”
Section: Metadata and Global Gene Expression In The Target Tissues Of Different Autoimmune Diseasesmentioning
confidence: 92%
“…A growing consensus suggests that inflammation is an important driver of type 1 diabetes mellitus and type 2 diabetes mellitus (T2DM) and associated vascular complications 5 . Inflammation in pancreatic islet β-cells results in cell depletion and loss of function 6 , 7 . Findings from experimental models and observational studies in humans demonstrate a key role for macrophages in islet β-cell inflammation in obesity and T2DM, driven largely by synergistic responses to IFNγ, TNF and IL-1β 8 .…”
Section: Inflammation and Metabolic Diseasementioning
confidence: 99%
“…The results of previous studies have been inconsistent with regards to whether increased WBC count contributes to DM prediction models independently of obesity 4 , 5 or whether elevated WBC count only reflects an increase in adipose tissue mass 6 . Increased BMI has been shown to be an essential contributor to DM through insulin resistance and islet β-cell failure 2 , 3 , 18 , 19 . Kashima et al reported that increased WBC count was predictive of type 2 DM, and that the combination of increased WBC count and BMI augmented the risk of DM, regardless of whether BMI was high or low 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation has been demonstrated to play a key role in the pathogenesis of type 2 diabetes mellitus (DM) 1 . Inflammation itself has been shown to cause insulin resistance 2 and promote β-cell death 3 . Previous studies have suggested an association between white blood cell (WBC) count, a non-specific parameter of inflammation, and incident DM 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%